IN VIVO PHARMACOKINETICS STUDY OF DICLOFENAC SODIUM LOADED BASELLA ALBA MUCILAGE BASED CARRIER FOR ENHANCEMENT OF ORAL BIOAVAILABILITY - CHOWDHURY, MOUMITA; DE, PINTU KUMAR (International Journal of Applied Pharmaceutics, 2025)
Objective: The present study aims to evaluate the in vivo bioavailability and pharmacokinetics of diclofenac sodium entrapped in a natural polysaccharide, Basella alba mucilage-based carrier. Methods: In this study, mucilage from Basella alba was chemically modified to improve its physicochemical properties and evaluated for its extent of modification by elemental analysis. The Diclofenac sodium-loaded sustained-release hydrogel bead developed from tailored Basella alba mucilage was evaluated for particle size, drug entrapment and Scanning electron microscopy. The resulting beads were used to assess the in vivo pharmacokinetics and bioavailability study. The pharmacokinetics of diclofenac sodium and diclofenac sodium loaded formulation were studied and compared with a marketed formulation of Diclofenac sodium (Subsyde®-CR DRCM capsule) at an equivalent dose in three groups of Wistar albino rats containing six rats in each group. Blood samples were collected via retro-orbital puncture for a period of 24 h. The diclofenac sodium concentration in a plasma sample of rats was detected by HPLC and the pharmacokinetic parameters were analyzed by noncompartmental modeling using PK solver. Results: The elemental analysis and degree of substitution confirmed the chemical modification of Basella alba mucilage. The Basella alba mucilage-based beads showed uniform surface with drug entrapment efficiency of 71.56%±0.85. The pharmacokinetic parameters of raw drug and test formulation showed significant difference (p<0.01), whereas test and marketed formulation appeared similar without any significant difference. The results showed higher mean residence time, increased tmax, and decreased Cmax of drug-loaded beads and marketed formulation than the pure drug. The relative bioavailability of Diclofenac sodium increased from 54.50% to 96.88% by entrapping it in Basella alba mucilage-based bead. Conclusion: Thus, the present work unfolded the potential of Basella alba mucilage as a bioavailability enhancer, advocating its use in developing novel pharmaceutical formulations.